Mathematics Education for Students with Autism Apectrum Disorders - Devi, Aribam Pratima (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
"The main goal of Mathematics education in schools is the mathematisation of a child‘s thinking."                                                        -National Curriculum Framework 2005 Autism spectrum disorder (ASD) is a developmental disorder which is neurological and lasts throughout a person's life affecting the overall health of the affected individual that is cognitive, emotional, social and physical aspects, beginning early in childhood. However, any individuals with ASD are found to exhibit intellectual abilities varying from person to person. This present paper attempts to study mathematics education for children with autism spectrum disorders. The researcher adopted a synthesis of literature review to study mathematics education and a systematic analysis of mathematics interventions for students with ASD. Limited number of Studies related to instructional interventions in mathematics was found for students with ASD. The need to receive help in studying of mathematics for students with ASD was highlighted. Interventions that targeted specific skill mathematics areas for individuals which were explicit and systematic were often found to be more effective. Repeated practice and rehearsal with specific targeted skills were recommended in order to be able to help the students with ASD achieve their academic goals in mathematics. Practical Implications for practitioners are also discussed which can help the students not only in strengthening their mathematics skills but also help in completing problems independently, and use acquired skills in applied settings or other community.